2D and 3D immunogold localization on (epoxy) ultrathin sections with and without osmium tetroxide. Issue 6 (14th February 2020) - Flechsler, Jennifer; Heimerl, Thomas; Pickl, Carolin; Rachel, Reinhard; Stierhof, York‐Dieter; Klingl, Andreas
Abstract: For nearly 50 years immunogold labeling on ultrathin sections has been successfully used for protein localization in laboratories worldwide. In theory and in practice, this method has undergone continual improvement over time. In this study, we carefully analyzed circulating protocols for postembedding labeling to find out if they are still valid under modern laboratory conditions, and in addition, we tested unconventional protocols. For this, we investigated immunolabeling of Epon‐embedded cells, immunolabeling of cells treated with osmium, and the binding behavior of differently sized gold particles. Here we show that (in contrast to widespread belief) immunolabeling of Epon‐embedded cells and of cells treated with osmium tetroxide is actually working. Furthermore, we established a "speed protocol" for immunolabeling by reducing antibody incubation times. Finally, we present our results on three‐dimensional immunogold labeling. Abstract : Immunogold labeling of Epon resin sections containing osmium tetroxide is possible and could be applied when structural details are relevant. Mostly, incubation times for immunogold labeling can be shortened without significant loss of efficiency. Three‐dimensional postembedding immunogold labeling was successfully applied on serial sections of a prokaryotic cell.